FORMATION OF THE READINESS OF FUTURE TEACHERS OF HIGHER EDUCATION INSTITUTIONS FOR SCIENTIFIC AND RESEARCH ACTIVITIES IN THE PROCESS OF BLENDED LEARNING: REGULATORY AND LEGAL PRINCIPLES AND BEST PRACTICES OF THE UNIVERSITY OF EDUCATION MANAGEMENT - Кириченко, Микола; Грицан, Олександр (Modern engineering and innovative technologies, 2024)
The publication examines the requirements of state regulatory and legal documents and analyzes the experience of the State Institution of Higher Education "University of Education Management" on the problem of forming the readiness of future teachers of i